Membangun Birokrasi yang Responsif melalui Implementasi Prinsip Serve Citizens, Not Customers di RSUD Berkah Kabupaten Pandeglang - Qothrunnada Hadid (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2024)
The health sector is an important pillar in a country's development. It has become an obligation for the government to provide quality health services that meet the needs of the community. To be able to design health services that suit the expectations and needs of the community, a responsive bureaucracy and community involvement are needed in every service process. The new public service paradigm is present as a relevant approach to realizing health services that are more community oriented. Therefore, this research aims to understand how the principle of Serve Citizens, Not Customers in the New Public Service is implemented in the context of health services and what obstacles are faced, specifically at Berkah Pandeglang Regional Public Hospital. This research uses a qualitative method where data collection is carried out through a literature study, observation, and interviews. The results of this research show that Berkah Pandeglang Regional Public Hospital has succeeded in implementing the principle of Serve Citizens, Not Customers from the New Public Service concept. Apart from that, good implementation has been seen in the aspects of fairness and personal attention. However, this research also identified that aspects of reliability and convenience still need to be optimized, and there are still several obstacles that must be faced to improve overall service quality. Keywords: Implementation, Public Services, Bureaucracy, New Public Service.